Rg3-enriched Korean Red Ginseng enhances blood pressure stability in spontaneously hypertensive rats - Harsha Nagar; Sujeong Choi; Saet-byel Jung; Byeong Hwa Jeon; Cuk-Seong Kim (Integrative Medicine Research)
Background: Korean Red Ginseng (Panax ginseng) has been shown to exert antihypertensive effects. In particular, ginsenoside Rg3 is thought to be a potent modulator of vascular function. The present study was performed to examine the antihypertensive efficacy of Korean Red Ginseng (KRG) extract and Rg3-enriched KRG (REKRG) extract. Methods: Spontaneously hypertensive rats (SHRs) and Wistar–Kyoto rats (WKYs) were divided into six groups (WKY control, WKY-KRG, WKY-REKRG, SHR control, SHR-KRG, and SHR-REKRG), and systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured at the carotid artery, followed by injection of 3 mg/kg KRG or 3 mg/kg REKRG. Results: REKRG treatment significantly decreased SBP and DBP 3 hours post-treatment in the SHR group compared with SHR control group. However, SBP and DBP were not significantly different in KRG-treated SHRs compared with control SHRs. REKRG treatment did not significantly alter SBP or DBP 3 hours post-treatment in the WKY group compared with WKY control group. Similarly, there were no differences in SBP or DBP with KRG treatment in the WKY group and WKY control group. Both KRG and REKRG increased endothelial nitric oxide synthase phosphorylation levels in the aorta, and the increases in endothelial nitric oxide synthase phosphorylation levels by REKRG treatment were higher than those with KRG treatment. Similarly, nitric oxide production in plasma from WKYs and SHRs was also increased by both KRG and REKRG. Conclusion: These results suggest that REKRG has a more beneficial effect on blood pressure control than KRG in SHRs.